TRANSFORMATION OF MASS CONSCIOUSNESS IN THE CONDITIONS OF THE COVID-19 PANDEMIC AND WAR: COGNITIVE AND GENDER ASPECTS OF DISTANCE LEARNING - Kobetіak, Andrii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
. The COVID-19 pandemic and wartime challenges have become key drivers of transformation in mass consciousness, reshaping communication, education, and cognitive processes. The expansion of distance learning has created new socio-psychological conditions, intensifying information flows and exposing individuals to cognitive overload and digital vulnerabilities. The aims and tasks. The study aims to analyze the impact of the pandemic and war on mass consciousness through distance learning, focusing on cognitive transformations and gender inequalities. The tasks include systematizing theoretical approaches and identifying asymmetries in access to digital educational resources. Research methods. The research is based on an interdisciplinary approach combining socio-cognitive analysis, gender theory, and a systemic perspective. Methods include comparative and content analysis, generalization of scientific sources, and interpretative analysis of cognitive and social transformations. Research results. The findings show that prolonged distance learning under crisis conditions modifies attention, memory, and critical thinking while increasing susceptibility to misinformation. Information overload and reliance on digital platforms contribute to cognitive fatigue and reduced learning effectiveness. Gender inequalities have also intensified due to unequal distribution of care work and limited access to technology. Discussion. Distance learning acts not only as an educational tool but also as a mechanism of cognitive influence, reflecting and reinforcing structural inequalities. The results align with existing research while highlighting the combined impact of the pandemic and war as underexplored. The study emphasizes the ambivalent nature of distance education, which expands access but deepens disparities. Conclusions. The research confirms that crisis-driven digitalization of education transforms mass consciousness, influencing cognition, behavior, and values. Distance learning is a key factor in shaping societal change. Strengthening media literacy, critical thinking, and gender-sensitive policies is essential for enhancing cognitive resilience and reducing inequalities in prolonged crises.